Propriedades estruturais, eletrônicas e caracterização de sítios ácidos e básicos de Lewis das redes metalorgânicas M2DEBDC (M = Mg, Co ou Mn e E = O ou S) - Aline de Oliveira (2018)
Metal-Organic Frameworks (MOFs) constitute a class of porous materials with a very large diversity of chemical structures. Therefore, the MOFs present promising characteristics to be used in gas storage,separation methods, as sensors, in controlled drugs release devices, as magnets, and in catalysis. The understanding of the chemical characteristics of these materials at molecular level can assist in thedesign of new MOFs with optimized properties to a specific purpose of use. A tool used to understand chemical processes at the molecular level is the computational simulation using the Density FunctionalTheory (DFT). The metal-organic frameworks of the chemical formula M2DEBDC (M = Mg, Co or Mn and E = O or S) consisting of the divalent metallic cations M(II) and the organic ligands DOBDC (2,5-dihydroxybenzene-1,4-dicarboxylate) or by DSBDC (2,5-disulfhydrylbenzene-1,4-dicarboxylate) exhibit very interesting characteristics. These MOFs have a high density of coordinatively unsaturated metallic sites in a well-determined chemical environment, besides having channels with diameters around 15 Å. Computational simulations of the MOFs M2DEBDC (M = Mg, Co or Mn and E = O or S)were performed using DFT. Different theoretical levels were investigated and the ones that provided data of the materials in better agreement with the literature were PBE-D2/US, PBE-D2+U4+J1/US andPBE-D2+U5,5+J0/US to the MOFs Mg2DEBDC, Co2DEBDC and Mn2DEBDC, respectively. The investigations indicated that the materials composed by the Mg(II) cations present the best Lewis acidicsites, whereas the ones composed by the ligand DSBDC present the Lewis basic sites most available to interactions with substrates. It has also been observed that these materials can be classified in thefollowing increasing order of structural flexibility to accommodate reagent molecules in their channels: Mg2DOBDC < Co2DOBDC < Mg2DSBDC _~ Co2DSBDC < Mn2DOBDC _~ Mn2DSBDC. An evaluation of these solids as catalysts for the cyanosilylation of aldehydes reaction was performed,which shows evidences of a superior catalytic performance of the MOF Mn2DOBDC in comparison to Mg2DOBDC, as it was experimentally observed. A preliminary investigation of the solids M2DEBDCas catalysts for the cycloaddition of carbon dioxide to epoxides was performed, indicating that the interaction of the CO2 molecules occurs with the Lewis basic sites of the MOFs, while the epoxidesinteract with the acidic sites.